Use of Limiting Dilution Method for Isolation of Nucleus Pulposus Mesenchymal Stem/Progenitor Cells and Effects of Plating Density on Biological Characteristics and Plasticity. (8th October 2017) - Lin, Linghan; Jia, Zhiwei; Zhao, Yachao; Wu, Yaohong; Zhao, Xiyan; Li, Yong; Guo, Ziming; Chen, Jiahai; Cheng, Shi; Wang, Deli; Ruan, Dike
Abstract : Objectives . To evaluate the effects of the limiting dilution method and plating density in rat nucleus pulposus mesenchymal stem/progenitor cells (NPMSCs). Materials and Methods . Nucleus pulposus tissues were isolated from 12-week-old male Sprague-Dawley rats and NPMSCs were isolated using limiting dilution method. Cells were then classified into 3 groups according to plating density. Cell morphologies were observed, and colony-forming units, migration abilities, proliferative capacities, cell cycle percentages, multilineage differentiation capacities, stem cell biomarker expression levels, and immunophenotyping were also examined in each group. Results . Low density group (LD) had higher morphological homogeneity, stronger colony-forming ability, higher cell proliferation capacity, and enhanced cell migration ability relative to the other two groups (p < 0.05 ). Moreover, LD had more cells entering S phase, with fewer cells arrested in G0/G1 phase (p < 0.05 ). While all three density groups showed a multilineage differentiation potential, LD showed a higher degree of observed and semiquantified lineage specific staining (p < 0.05 ). Furthermore, LD displayed higher expression levels of stem cell biomarkers (Nanog, Oct4, and Sox2) and showed higher percentages of CD29+, CD44+, and CD90+ cells (p < 0.05 ) following flow cytometry analysis. Conclusions . Limiting dilution method is suggested when isolating NPMSCs as a means of improving cell activity and plasticity.